2016
DOI: 10.1177/1040638716638126
|View full text |Cite
|
Sign up to set email alerts
|

Renal leiomyosarcoma in a cat

Abstract: Renal leiomyosarcoma was diagnosed in a 10-year-old Domestic Shorthair cat with a 3-year history of clinically managed, chronic renal disease. Sudden death was preceded by a brief episode of mental dullness and confusion. At postmortem examination, the gross appearance of the left kidney was suggestive of hydronephrosis, and a nephrolith was present in the contralateral kidney. However, histology revealed an infiltrative, poorly differentiated, spindle cell sarcoma bordering the grossly cavitated area. Neoplas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 31 publications
0
13
0
2
Order By: Relevance
“…3,4,12 In a study that included 1129 feline cases of intestinal neoplasia, only 14 were diagnosed with leiomyosarcoma (1.2%), with equal frequency in the colon and the small intestine. 3 There are reports of feline non-intestinal leiomyosarcomas, such as those involving the urinary bladder, 13 kidney, 14 female reproductive tract 15 and liver. 16 There are no reported cases of feline gastric leiomyosarcoma.…”
Section: Discussionmentioning
confidence: 99%
“…3,4,12 In a study that included 1129 feline cases of intestinal neoplasia, only 14 were diagnosed with leiomyosarcoma (1.2%), with equal frequency in the colon and the small intestine. 3 There are reports of feline non-intestinal leiomyosarcomas, such as those involving the urinary bladder, 13 kidney, 14 female reproductive tract 15 and liver. 16 There are no reported cases of feline gastric leiomyosarcoma.…”
Section: Discussionmentioning
confidence: 99%
“…The most common primary renal tumour is lymphosarcoma, which in most cases is bilateral, followed by renal carcinomas that are usually unilateral (Gabor, Malik & Canfield 1998 ; Henry et al 1999 ). Additional primary renal tumours that have been demonstrated in cats include transitional cell carcinoma (Hanzlicek et al 2012 ), cystadenoma (Mosenco et al 2008 ), squamous cell carcinoma (Gomez Selgas, Scase & Foale 2014 ), adenoma (Clark & Wilson 1988 ), leiomyosarcoma (Evans & Fowlkes 2016 ); adenocarcinoma (Britt, Ryan & Howard 1985 ) and nephroblastoma (Henry et al 1999 ), with none reported to be paragangliomas. Bilateral renal carcinomas were demonstrated in a case report in one cat (Steinberg & Thomson 1994 ).…”
Section: Discussionmentioning
confidence: 99%
“…Aufgrund der histopathologischen Charakteristika und des immunhistochemischen Expressionsmusters handelte es sich in allen vier FĂ€llen vermutlich um Leiomyosarkome. Sie wiesen histomorphologisch weitgehende Ähnlichkeiten mit den in der Literatur bei Hund und Katze beschriebenen EinzelfĂ€llen derartiger Neoplasien auf (13,28,37,38). Beim Menschen sind primĂ€re renale pleomorphe Sarkome selten, wobei es sich in 50-60 % der FĂ€lle um Leiomyosarkome handelt (33,42…”
Section: Histopathologische Und Immunhistochemische Untersuchungsbefundeunclassified